Etiology of post-harvest diseases caused by Fusarium species in tomato - Ismaila, Abubakar Abubakar (2013)
Fusarium species is one of the common pathogens of post-harvest spoilage to cause fruit rots on tomato and other perishable vegetable fruits. The objectives of this study were to determine the diversity of Fusarium species isolated from post-harvest fruit rots of tomato, to identify the causal organism based on their phenotypic characteristics, to verify the pathogen of Fusarium fruit rot of tomato based on pathogenicity test and to classify the Fusarium isolates into vegetative compatibility groups (VCGs). Carnation leaf-piece agar (CLA) and potato dextrose agar (PDA) media were used for phenotype-based identification of the Fusarium isolates with emphasis for characterizations of the shapes and sizes of the macroconidia and microconidia, colony features, growth rates and chlamydospores. A total of 180 Fusarium isolates were obtained from 13 locations throughout Selangor. F. solani was most abundantly isolated (34%) followed by F. semitectum (31%), F. oxysporum (31%), F. subglutinans (3%) while the least was F. equiseti (1%). Twenty seven isolates were tested for pathogenicity test by injecting 1 ml of the conidial suspension onto healthy tomatoes. All the tested Fusarium isolates were pathogenic on tomato with different severity levels. The non-inoculated control fruits were injected with the sterile water showed no any symptoms of fruit rot. The most virulent was F. oxysporum (isolate B711T) with disease severity index (DSI) 93.75%, while the least were F. solani (isolate B647T) and F. oxysporum (isolate B727T) with DSI of 37.50%. All Fusarium isolates were then classified into VCGs which were F. oxysporum (10 VCGs), F. semitectum (3 VCGs) and F. subglutinans (2 VCGs). The isolates of F. oxysporum were genetically diverse as depicted by the index and distribution of the VCGs. However, there was no strong correlation observed between VCGs of all three species and locations.